ALK-Testing in non-small cell lung cancer (NSCLC): Immunohistochemistry (IHC) and/or fluorescence in-situ Hybridisation (FISH)?: Statement of the Germany Society for Pathology (DGP) and the Working Group Thoracic Oncology (AIO) of the German Cancer Society e.V. (Stellungnahme der Deutschen Gesellschaft für Pathologie und der AG Thorakale Onkologie der Arbeitsgemeinschaft Onkologie/Deutsche Krebsgesellschaft e.V.). (January 2017) - von Laffert, M.; Schirmacher, P.; Warth, A.; Weichert, W.; Büttner, R.; Huber, R.M.; Wolf, J.; Griesinger, F.; Dietel, M.; Grohé, Ch.
Highlights: FISH and IHC are available as validated diagnostic procedures. At individual centers additional NGS-based procedures can be performed. ALK-IHC is at least equivalent to FISH for ALK-activation in NSCLC. Two validated antibodies (5A4 and D5F3) are presently available. Antibodies should be used according to the validation studies. Abstract: The EML4-ALK pathway plays an important role in a significant subset of non-small cell lung cancer patients. Treatment options such as ALK tyrosine kinase inhibitors lead to improved progression free survival and overall survival. These therapeutic options are chosen on the basis of the identification of the underlying genetic signature of the EML-ALK translocation. Efficient and easily accessible testing tools are required to identify eligible patients in a timely fashion. While FISH techniques are commonly used to detect this translocation, the broad implementation of this type of ALK testing into routine diagnostics is not optimal due to technical, structural and financial reasons. Immunohistochemical techniques to screen for EML4-ALK translocations may therefore play an important role in the near future. This consensus paper provides recommendations for the test algorithm and quality of the respective test approaches, which are discussed in the light of the current literature.